Altered Hippocampal Subfields Volumes Is Associated With Memory Function in Type 2 Diabetes Mellitus - Li, Mingrui; Li, Yifan; Liu, Yujie; Huang, Haoming; Leng, Xi; Chen, Yuna; Feng, Yue; Ma, Xiaomeng; Tan, Xin; Liang, Yi; Qiu, Shijun (Frontiers in Neurology, 2021)
Objective: Cognitive impairment in type 2 diabetes mellitus (T2DM) patients is related to changes in hippocampal structure and function. This study explored morphological alterations in the hippocampus and subfields in T2DM patients and their relationship with cognitive function. Methods: Thirty T2DM patients and twenty healthy controls (HCs) were recruited and underwent rest-state functional magnetic resonance imaging (rs-fMRI) and a sequence of cognitive tests. Freesurfer 6.0 was performed to segment the hippocampus into twelve subregions automatically. Then relationships between hippocampal subfield volumes and neurocognitive scale scores in the T2DM group were evaluated. Results: Immediate memory scores on the auditory verbal learning test (AVLT) and Montreal Cognitive Assessment (MoCA) scores in T2DM patients were lower than in the HCs. T2DM patients showed lower volumes in the bilateral molecular layer, granule cell and molecular layer of the dentate gyrus (GC-ML-DG), cornu ammonis 4 (CA4), fimbria, left subiculum and right hippocampus amygdala transition area (HATA) compared to HCs. Volume of R-HATA was correlated positively with AVLT (immediate) scores (r=0.427, p=0.03). Conclusion: Hippocampal subfield atrophy in T2DM patients showed a specific regional distribution. These subfield volumes are related to cognitive ability in T2DM patients, suggesting that degeneration in specific hippocampal subfields may be the main potential mechanism of cognitive dysfunction in these patients. Additionally, these specific regional distributions were similar to those observed in Alzheimer's disease (AD), which may partially explain why T2DM is an important risk factor for AD.